A Hybrid Perovskite Solar Cell Modified With Copper Indium Sulfide Nanocrystals to Enhance Hole Transport and Moisture Stability. Issue 8 (20th July 2017) - Ma, Yingzhuang; Vashishtha, Parth; Shivarudraiah, Sunil B.; Chen, Kai; Liu, Ye; Hodgkiss, Justin M.; Halpert, Jonathan E.
Abstract : Lead halide perovskite solar cells have attracted tremendous attention for their impressive power conversion efficiencies. However, stability is still one of the most significant concerns for perovskite solar cells. Here, a layer of copper indium sulfide nanocrystals (CIS NCs) has been introduced into the perovskite solar cell, giving rise to enhanced charge transfer property as well as longer lived films and devices. Ultrafast photoluminescence studies on the charge transfer behavior have revealed that the CIS NC layer can modify the interface between perovskite and hole transporting material, suppressing charge recombination pathways. The degradation mechanism in this system is also studied under various simulated environmental conditions. Devices without CIS NCs show significant degradation after exposure to high humidity (over 80%) without device encapsulation. In contrast, the perovskite thin films with a CIS layer show superior resistance to humidity, while perovskite‐CIS NC solar cells exhibit significantly improved photovoltaic stability. Abstract : Copper indium sulfide nanocrystals are employed as a post‐deposition alteration to the perovskite thin film in perovskite solar cells, showing longer device stability under high humidity condition, without introducing extra resistance for charge transportation, but helping inhibiting the recombination process.